AN ANALYSIS OF THE EFFECT OF SOCIAL MEDIA MARKETING AND STORE ATMOSPHERE ON REPURCHASE DECISIONS MEDIATED BY BRAND IMAGE: EVIDENCE FROM LOYALTY FORSURE CONSUMERS IN MAKASSAR CITY - Rusman DH, Khutbah Nur; Anwar, Anwar; Abadi, Rahmat Riwayat (Universitas Negeri Makassar, 2026)
Abstract: This study examines the effects of locus of control and time management on academic stress among working students, with peer social support serving as an intervening variable. The study involved 169 working students selected through purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1. The analytical procedures included validity and reliability testing, structural model analysis, and testing of direct and indirect effects. The findings indicate that locus of control and time management significantly influence academic stress, both directly and indirectly through peer social support. These results highlight the importance of strengthening personal self-regulation capacities and fostering supportive peer environments to reduce academic stress among working students.Keywords: Social Media Marketing, Store Atmosphere, Brand Image, Repurchase Decision, Loyalty Forsure